Olfactory Memory Impairment Differs by Sex in a Rodent Model of Pediatric Radiotherapy - Perez, Emma C.; Rodgers, Shaefali P.; Inoue, Taeko; Pedersen, Steen E.; Leasure, J. Leigh; Gaber, M. Waleed (Frontiers in Behavioral Neuroscience, 2018)
Although an effective treatment for pediatric brain tumors, cranial radiation therapy (CRT) damages surrounding healthy tissue, thereby disrupting brain development. Animal models of pediatric CRT have primarily relied on visual tasks to assess cognitive impairment. Moreover, there has been a lack of sex comparisons as most research on the cognitive effects of pediatric CRT does not include females. Therefore, we utilized olfaction, an ethologically relevant sensory modality, to assess cognitive impairment in an animal model of CRT that included both male and female mice. Specifically, we used the novel odor recognition (NOdorR) task with social odors to test recognition memory, a cognitive parameter that has been associated with olfactory neurogenesis, a form of cellular plasticity damaged by CRT. In addition to odor recognition memory, olfactory ability or discrimination of non-social and social odors were assessed both acutely and 3 months after CRT. Magnetic resonance imaging (MRI) and histology were performed after behavioral testing to assess long-term damage by CRT. Long-term but not acute radiation-induced impairment in odor recognition memory was observed, consistent with delayed onset of cognitive impairment in human patients. Males showed greater exploration of social odors than females, but general exploration was not affected by irradiation. However, irradiated males had impaired odor recognition memory in adulthood, compared to non-irradiated males (or simply male controls). Female olfactory recognition memory, in contrast, was dependent on estrus stage. CRT damage was demonstrated by 1) histological evaluation of olfactory neurogenesis, which showed a reduction in CRT versus control, and 2) imaging analyses which showed that the majority of brain regions were reduced in volume by CRT. Specifically, two regions involved in social odor processing (amygdala and piriform cortex) were damaged by cranial irradiation in males but not females, paralleling olfactory recognition findings.